Burnout syndrome in teachers of public schools in Buenópolis, MG, Brazil - Araújo, Valéria Alaide; Freire, Jéssica Magalhães; Oliveira, Marcos Vinícius Macedo de (Journal of Health Care, 2017)
Introduction: The burnout syndrome is associated with work. In this environment, there may be activities that cause psychophysical maladjustment in workers. Its incidence is higher among professionals who have direct relationships with people, such as teachers, who live daily with factors that contribute to mental and physical fatigue. Objective: To analyze the occurrence of burnout syndrome among teachers in the city of Buenópolis, Minas Gerais, Brazil, checking if there is any association with sociodemographic characteristics and work of these professionals. Materials and methods: This is an analytical, transversal and quantitative study on a sample of 71 teachers. Some research tools were used, such as socioeconomic forms, labor and MBI (Maslach Burnout Inventory) that identified characteristics and the occurrence of burnout syndrome. Results: It was found that 52.1% of the teachers have burnout syndrome, and a higher incidence of this was observed among individuals who feel undervalued (p=0.001), with little autonomy (p=0.000), who do not like the job (p=0.014), and have thought of giving up the profession (p=0.000). Conclusion: The teaching profession can generate great stress, and the analysis of this study shows that more than half of the teachers analyzed presented burnout syndrome. There is a need for improvement in the organizational environment keeping in mind the factors related to the disease, since it causes health problems and affects teacher performance, hampering the educational system. We suggest, as a way to improve conditions, the psycho-pedagogical supervision as prophylactic treatment.